Performance Evaluation of Tourism Human Resource Management Based on Fuzzy Data Mining - Fei Wei (Journal of Mathematics)
Tourism human resources performance management is an important means of enterprise core competitiveness; the assessment results is good or bad will directly affect the staff's work enthusiasm and attitude; the use of tourism human resources, configuration, and performance carries on the scientific, reasonable, and effective comprehensive evaluation and can fully stimulate the potential of employees. To continuously improve the work efficiency, quality, and level of staff, which has certain application value and practical significance for the long-term and healthy development of tourism industry, this article analyzes the current situation of tourism human resource performance management, introduces the data mining technology and fuzzy data mining technology, and then gives the fuzzy data mining algorithm and detailed fuzzy data mining steps, through the fuzzy data mining technology to evaluate the performance of tourism human resource management. It also analyzes the key factors and existing problems of human resource management in tourism industry and puts forward innovative thinking countermeasures for the performance management of human resources in the tourism industry.